If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -10 = 2x + 50 Reorder the terms: -10 + 4x = 2x + 50 Reorder the terms: -10 + 4x = 50 + 2x Solving -10 + 4x = 50 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -10 + 4x + -2x = 50 + 2x + -2x Combine like terms: 4x + -2x = 2x -10 + 2x = 50 + 2x + -2x Combine like terms: 2x + -2x = 0 -10 + 2x = 50 + 0 -10 + 2x = 50 Add '10' to each side of the equation. -10 + 10 + 2x = 50 + 10 Combine like terms: -10 + 10 = 0 0 + 2x = 50 + 10 2x = 50 + 10 Combine like terms: 50 + 10 = 60 2x = 60 Divide each side by '2'. x = 30 Simplifying x = 30
| 9/8-1/4-2/3 | | 3(2+y)-4=10 | | -5a+6=15 | | (5x+2y)(5x-2y)=25x^2-4y^2 | | (x-8)+(9x-2)+36=360 | | X-23=105 | | 13/15-7/10 | | 3w+7=16 | | -5a+6=12 | | 19x+6=44 | | 24-5x=24-9x | | 4=-16t^2+45t+6 | | 3y=4t/y^2 | | 42=-16t^2+60t+6 | | 3y=(4t/y~2) | | 45=-16t^2+60+6 | | 4x^2+32x=-23 | | 35=-16t^2+60+6 | | 3(x-2)+5(x-2)=15x | | -9x+y=52 | | 42=-16t^2+60+6 | | 26-r=2r+2 | | (3x+1)+55=x | | 40=-16t^2+60+6 | | -2(13-m)=(m-19)-6 | | 12r+30-72=0 | | 100x+7x=111.28 | | 129+3x=x | | 40=-16t^2+46+6 | | 2r+26=r-2 | | 42=-16t^2+46+6 | | y=2(x-4)(x+2) |